Bibliometric Analysis of Islamic Finance: Mapping Growth and Research Trends - Kumara, Gatot Kunta; Nugraha, Nugraha (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
Islamic finance, a rapidly expanding sector, integrates financial principles with Islamic moral and ethical guidelines derived from the Quran and Hadith. This study conducts a thorough analysis of literature reviews in this field to discern its growth and collaborative dynamics. The primary objective of this research is to analyze literature reviews on Islamic finance using the Scopus database, thereby providing insights into publication trends, influential countries, and emerging research themes. An initial dataset of 231 publications was extracted from the Scopus database and refined to 139 publications for detailed bibliometric analysis using VOSviewer software. The analysis revealed that the year 2023 had the highest number of journal publications, totaling 21 articles, while the highest citation count, 221, was recorded in 2014. These publications are globally dispersed across America, Asia, Africa, Australia, and Europe. The most influential countries with substantial international collaboration include the United States, Indonesia, the United Kingdom, Saudi Arabia, and Malaysia. The study concludes that Islamic finance is a burgeoning financial market segment that promotes equitable financial and economic frameworks. The increasing demand for Sharia-compliant financial products and the advancement of Islamic financial institutions are noteworthy trends. The findings offer deeper insights into the evolution of Islamic finance research, identify centers of excellence, and delineate current research trends. This foundational framework will assist researchers, practitioners, and academics in navigating the future development of Islamic finance research, thereby fostering growth and innovation in the field.========================================================================================================ABSTRAK – Analisis Blibliometrik Keuangan Islam: Pemetaan Perkembangan dan Tren Riset. Sistem keuangan Islam, dalam praktiknya, mengintegrasikan nilai-nilai moral dan etika Islam yang bersumber dari Al-Quran dan Hadits. Penelitian ini melakukan analisis menyeluruh terhadap tinjauan literatur di bidang ini untuk memahami perkembangan dan dinamika kolaborasinya. Tujuan utamanya adalah menganalisis tinjauan literatur terkait keuangan Islam menggunakan basis data Scopus, untuk mendapatkan gambaran tentang tren publikasi, negara-negara berpengaruh, dan tema penelitian yang muncul. Dataset awal sebanyak 231 publikasi diekstraksi dan disaring menjadi 139 publikasi untuk analisis bibliometrik menggunakan aplikasi VOSviewer. Hasil analisis menunjukkan bahwa tahun 2023 memiliki jumlah publikasi tertinggi, yaitu 21 artikel, sementara jumlah sitasi tertinggi (221) tercatat pada tahun 2014. Publikasi ini tersebar di berbagai benua, dimana negara-negara yang paling berpengaruh dengan kerjasama internasional yang signifikan adalah Amerika Serikat, Indonesia, Inggris, Arab Saudi, dan Malaysia. Penelitian ini menyimpulkan bahwa keuangan Islam merupakan segmen pasar keuangan yang berkembang pesat yang mempromosikan kerangka keuangan dan ekonomi yang adil. Permintaan yang meningkat untuk produk-produk keuangan yang sesuai Syariah dan perkembangan lembaga keuangan Islam adalah tren yang patut menjadi perhatian. Temuan ini memberikan pemahaman yang lebih dalam tentang evolusi penelitian keuangan Islam, mengidentifikasi pusat-pusat keunggulan, dan menjelaskan tren penelitian saat ini. Kerangka dasar ini akan membantu peneliti, praktisi, dan akademisi dalam menavigasi perkembangan masa depan penelitian keuangan Islam, sehingga mendorong pertumbuhan dan inovasi di bidang ini.